ANALISIS PRODUCTIVE MAINTENANCE PADA MESIN WELDING POLARIS DI PT EXCELITAS - Firmansyah, Ikhsan; Sirait, Ganda (Computer Science and Industrial Engineering, 2025)
This study aims to analyze the performance of the Polaris Welding machine at PT Excelitas using the Mean Time Between Failure (MTBF), Mean Time To Repair (MTTR), and Overall Availability methods. The Polaris Welding machine often experiences downtime, so that productivity is disrupted. The results of the study showed an average MTBF value of 3.24 hours, MTTR of 0.55 hours, and overall availability of 84.66%, which is still below the global standard (≥ 90%). The main causal factors are lack of operator training, unscheduled machine maintenance, and material mismatch. To improve machine performance, planned maintenance standards and autonomous maintenance are recommended. This approach is expected to minimize downtime and increase the effectiveness of the production process at PT Excelitas.